INSEF-ExpoQuim: assessing the exposure of the Portuguese population to chemicals - Namorado, Sónia (2020)
Introduction: Exposure to hazardous chemicals may endanger human health and pollute the environment. To assess and minimize the risks associated with the use of chemicals it is essential to know whether and to what extent these substances are present in the human body. We report preliminary results of the recruitment phase in the study of Exposure of the Portuguese Population to Environmental Chemicals: a study nested in INSEF 2015 (INSEF-ExpoQuim). Methods: INSEF-ExpoQuim is an epidemiologic study nested in INSEF 2015 targeting 300 non-institutionalized individuals aged 28-39 years, living in Portugal for more than 12 months, able to follow an interview in Portuguese. Fieldwork started in June 2019 and is ongoing. Procedures are according to the guidelines of the HBM4EU project. Selected individuals receive an invitation letter and are later contacted by phone to schedule sample collection and the telephone interview. Urine samples for determination of heavy metals, bisphenols and Polycyclic Aromatic Hydrocarbons are collected, as well as data on socio-demographic characteristics, living conditions and residential history, habits/lifestyle, nutrition, health, occupation and substance specific information covering nearly all exposure pathways. Results: Up to date 384 of the 848 eligible individuals were successfully contacted (45,3%), of which 172 accepted to participate in INSEF-ExpoQuim corresponding to a participation rate of 20%. Conclusions: Results from INSEF-ExpoQuim will contribute to reduce the health impact that could result from the exposure of the population residing in Portugal to environmental chemicals, by producing high quality data on the actual exposure of the Portuguese population to hazardous chemicals, in order to support the development and implementation of policy measures aimed at minimizing exposure to those chemicals.